A Infra-estrutura do Texto Multimodal - Leal, Audria Albuquerque (2016)
This research has been financed by Portuguese National Funding through the FCT Fundação para a Ciência e Tecnologia as part of the project of the Centro de Linguística da Universidade Nova de Lisboa (UID/LIN/03213/2013) and also the Grant SFRH/BPD/111234/2015.